2018
DOI: 10.1016/j.bbmt.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Platelet-Derived Growth Factor Receptor Alpha Chain Antibodies Predict for Response to Nilotinib in Steroid-Refractory or -Dependent Chronic Graft-Versus-Host Disease

Abstract: Imatinib has clinical activity in chronic graft-versus-host disease (cGVHD), a significant complication of allogeneic hematopoietic cell transplant. Nilotinib is a tyrosine kinase inhibitor that targets the same receptors as imatinib but with different affinities. We tested the hypothesis that nilotinib is safe and has clinical activity in cGVHD. Thirty-three participants were enrolled in a phase I/II dose escalation and dose extension clinical trial of nilotinib for the treatment of steroid-refractory or- dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…[33][34][35][36][37] It is also possible that a higher frequency of TKI use after RIC allo-HCT for treatment or prevention of CML relapse may have curbed the cGVHD risk. [38][39][40] In multivariable analysis, no significant interaction was found between conditioning intensity and disease status at the time of allo-HCT. The survival outcomes in patients who were in AP or CP21 at allo-HCT were not significantly different between the conditioning cohorts.…”
Section: Discussionmentioning
confidence: 87%
“…[33][34][35][36][37] It is also possible that a higher frequency of TKI use after RIC allo-HCT for treatment or prevention of CML relapse may have curbed the cGVHD risk. [38][39][40] In multivariable analysis, no significant interaction was found between conditioning intensity and disease status at the time of allo-HCT. The survival outcomes in patients who were in AP or CP21 at allo-HCT were not significantly different between the conditioning cohorts.…”
Section: Discussionmentioning
confidence: 87%
“…Chronic GVHD is an autoimmune-like syndrome caused by the interactions of donor CD4 + T and B cells and production of IgG (7)(8)(9)(10)(11). Recently, antibodies have been reported to play an important role in the development of cGVHD (12)(13)(14)(15)(16)(17)(18)(19). Previous studies showed that donor B cellderived antibodies augmented the development of bronchiolitis obliterans and perpetuated cutaneous cGVHD in mice (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…GvHD was the leading cause of death with an incidence comparable to that observed in patients not treated with 2GTKIs [ 13 , 31 , 32 ] (50/383 patients,13%), followed by infections. Given the increasing experience on the efficacy of TKIs as GvHD treatment [ 39 41 ], the question of influence of the immunomodulatory potency of TKIs [ 42 48 ] on GvHD incidence and severity could be raised. Significantly lower incidence of cGvHD in patients pre-treated with imatinib compared with a historical group control has been reported [ 15 ], but it can be attributed to differences in GvHD prophylaxis and mainly a more frequent use of antithymocyte globulin in imatinib group.…”
Section: Discussionmentioning
confidence: 99%